The Song #2019GantiPresiden and Political Communication in Simulacra Analysis - Dani Fadillah; Jian Chang (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2021)
This research aims to find out how the hashtag #2019GantiPresiden, which was initially just a common hashtag on Twitter, has triggered a massive mass movement in Indonesia. Moreover, the hashtag incarnated into various souvenirs, even into a song that shouted the need for Indonesia to have a new president. The Hashtag #2019GantiPresiden became a medium of communication to convey political messages from political actors and those interested in the Indonesian presidential elections in 2019. Qualitative method was used in the drafting of this paper by collecting data relating to the topic of discussion and then using the Simulacra logic initiated by Jean Baudrillard in data analysis. The study concluded that in 2019, the #2019GantiPresiden hashtags showed the world that a voice on social media could become a great mass power in the real world.